Effectiveness of psychospiritual adaptation to cardiac rehabilitation compared to standard cardiac rehabilitation for post coronary angioplasty patients in Hospital Universiti Sains Malaysia - Yusof, Norizam Muhammad (2024)
Previous literatures have documented evidence of heightened anxiety and depression experienced by patients with coronary heart disease (CHD) after coronary angioplasty procedures. This underscores the need for comprehensive psychological intervention in cardiac rehabilitation programs, with an emphasis on integrating psychospiritual elements. Consequently, this research aimed to develop a cardiac rehabilitation program with psychospiritual adaptation (CR-PS) module incorporating Islamic mindfulness relaxation techniques. The study involved 30 CHD patients randomly assigned to intervention (CR-PS program) and control (standard cardiac rehabilitation – SCR program) groups. Over a three-month period, data on systolic/diastolic blood pressure, pulse rate, anxiety, and serum cortisol levels were collected at three intervals. Repeated ANOVA assessments revealed significant reductions in the intervention group and increases in the control group across these parameters. Specifically, systolic blood pressure decreased from 132.47 to 121.73 in the intervention group compared to an increase from 127.33 to 132.00 in the control group. Similar trends were observed for diastolic blood pressure and pulse rate. Anxiety levels decreased from 14.60 to 10.80 in the intervention group, contrasting with a minor change in the control group. Serum cortisol levels decreased in the intervention group (7.40 to 5.20) but remained stable in the control group. While no significant differences were found in serum creatinine kinase, CKMB, and depression levels, the intervention group showed a decline in these parameters compared to an increase in the control group. Overall, the study suggests that integrating psychospiritual elements into cardiac rehabilitation is effective for CHD patients, and the developed module can serve as a basis for the adaptation of psychospiritual interventions in rehabilitation process during recovery period.